Implementasi Pengelolaan Kesiswaan dalam Peningkatan Kualitas Pendidikan Berdasarkan Instrumen Akreditasi Satuan Pendidikan Tahun 2022 Di MIN 1 Kota Bandung - Fina Ariatpi; Mulyawan Safwandy Nugraha (JURNAL MAPPESONA, 2024)
This study aims to analyze the implementation of student management in an effort to improve the quality of education at MIN 1 Bandung City based on the Education Unit Accreditation Instrument (IASP) in 2022. The research method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation studies. The results showed that MIN 1 Bandung City has implemented student management in accordance with IASP 2022 standards, but there are still several aspects that need to be improved to achieve optimal education quality.